Comparative Approaches to Informal Housing Around the Globe - Grashoff, Udo (Fringe, 2020)
Comparative Approaches to Informal Housing Around the Globe brings together historians, anthropologists, political scientists, sociologists, urban planners and political activists to break new ground in the globalisation of knowledge about informal housing. Providing both methodological reflections and practical examples, they compare informal settlements, unauthorised occupation of flats, illegal housing construction and political squatting in different regions of the world. Subjects covered include squatter settlements in Kyrgyzstan and Kazakhstan, squatting activism in Brazil and Spain, right-wing squatting in Germany, planning laws and informality across countries in the Global North, and squatting in post-Second World War UK and Australia.